Chemical Examination of Methanyl Yellow in Processed Food Products at the Blumbungan Market Pamekasan District - Kamilia, Lia; Hefdiyah (Bioconsortium : Biological Research and Education, 2024)
Non-food grade dyes such as textile dyes are widely used by rogue manufacturers to give color to their food products. The example is textile dyes methanyl yellow. Methanyl yellow is made from methanylic acid and diphenylamine. Both of these ingredients are toxic. This research is used the metanyl yellow rapid test kit method by taking several types of food samples suspected of containing metanyl yellow. From the three samples such as chicken skin, rambak crackers and color crackers, there are two samples positive for methanyl yellow, chicken skin and color crackers. This is expressed by a change in the color of the yellow reagent to purple. Based on the research, it can be concluded that there are 2 types of samples containing methanyl yellow dye at the Blumbungan market in Pemekasan Regency.